PERSEPSI SISWA TERHADAP POSISI AKAL DAN WAHYU DALAM PARADIGMA KEILMUAN ISLAM DI ERA MODERN - Muh. Nawir; Esby Eriyanti Nuzulia; Rosmiati Daya; A. Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims at finding out the students' perceptions of the relationship between reason and revelation within the Islamic scientific paradigm, and how this understanding influences their thinking about science and spiritual values ​​in the modern era. The method used in this study is a qualitative descriptive approach with data collection techniques through questionnaires, interviews, and observations. This study was conducted at Muhammadiyah 1 High School in Makassar with a sample of 30 students. The results show that the majority of students understand reason and revelation as two complementary sources of knowledge. However, there is a tendency for some students to still separate rationality and religiousness in understanding science. This study emphasizes the need to integrate Islamic values ​​and rationality in the learning process to form a complete Islamic scientific paradigm.